Ionic Liquids: Past, present and future - Austen Angell, C; Ansari, Younes; Zhao, Zuofeng (Faraday discussions, 2012)
An overview of the field of low-melting ionic liquids is given from its inception in 1886 through to the present time. The subject is divided into an introductory section that summarizes the early history of the field, and differentiates its sub-sections, before addressing matters judged of some interest in "pre-surge" and "post-surge" stages of its development, focusing on physicochemical as opposed to the prolific synthetic and industrial aspects in which the author has no competence. We give a final section specifically to protic ionic liquids, which we consider to have particular scientific potential.